2022
DOI: 10.1002/adma.202203401
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Switch‐Embedded Solution‐Processed Semiconductors

Abstract: oxides, [44][45][46][47][48] inorganic nanocrystals, [49][50][51][52][53] and quantum dots. [54][55][56][57] The cornerstones in the history of these solution-processed semiconductors are as follows: 1) understanding of the fundamental physics of processes such as charge generation and transport; 2) optimization of their electronic/optoelectronic performances based on the development of new materials and/ or device architectures; 3) development of further functionalities of these materials typically by embeddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 228 publications
0
6
0
Order By: Relevance
“…37 The process of blending is aimed at avoiding phase segregation while favoring intermixing towards a maximal degree of intercomponent interfacing, as inspired by van der Waals heterostructures. 43 In our photoswitchable blend, the pgBTTT polymer imparts mixed ionicelectronic conductivity whereas the OEG-SP additive confers a photoresponsive nature to the hybrid material. These two components have been mixed in a 20% m/m proportion of OEG-SP in pgBTTT and deposited as drop-cast thin films from CHCl 3 solutions at various concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…37 The process of blending is aimed at avoiding phase segregation while favoring intermixing towards a maximal degree of intercomponent interfacing, as inspired by van der Waals heterostructures. 43 In our photoswitchable blend, the pgBTTT polymer imparts mixed ionicelectronic conductivity whereas the OEG-SP additive confers a photoresponsive nature to the hybrid material. These two components have been mixed in a 20% m/m proportion of OEG-SP in pgBTTT and deposited as drop-cast thin films from CHCl 3 solutions at various concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Benefiting from the designability and flexibility of organic semiconductor materials, organic memory devices have garnered widespread attention and development to meet the ever-growing demand for high storage density. [6][7][8][9] Among various types of devices, field-effect floating gate transistor memories are promising due to their ability to preserve charge-trapping centers within the device, preventing slow release of charges and thus achieving robust storage capabilities. [10][11][12][13] Moreover, unlike traditional electrically programmable memory devices that read information, fieldeffect floating gate transistors involve a charge-trapping layer that can form an additional control electric field by capturing photogenerated carriers, providing a degree of freedom in the optical control of storage capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 , 21 , 22 ] One widely accepted approach for achieving multifunctionality in OFETs involves incorporating molecular switches capable of inducing transitions between two or more metastable isomers through light stimuli. [ 23 , 24 ] Previous studies have shown that integrating a molecular switch within an OSC facilitates effective control of trap levels, thereby resulting in photoprogrammable OFETs. [ 25 , 26 , 27 , 28 , 29 ] Among the photochromic molecular switches commonly used in combination with OSCs, diarylethenes (DAEs) have emerged as a prominent choice.…”
Section: Introductionmentioning
confidence: 99%